ANALISIS KESALAHAN BERBAHASA PADA BUKU SISWA KURIKULUM 2013 TEMA “LINGKUNGAN SAHABAT KITA” KELAS V SEKOLAH DASAR - Rizka Nur Oktaviani; Melindha Dia Ayu Wulandari (Universitas Sarjanawiyata Tamansiswa, 2021)
The problem that would be examined in this research was analyzing language errors in the use of letters and punctuation in the 2013 curriculum student book with the theme